Advances in Structural Biology and the Application to Biological Filament Systems. (27th February 2018) - Popp, David; Koh, Fujiet; Scipion, Clement P. M.; Ghoshdastider, Umesh; Narita, Akihiro; Holmes, Kenneth C.; Robinson, Robert C.
Abstract : Structural biology has experienced several transformative technological advances in recent years. These include: development of extremely bright X‐ray sources (microfocus synchrotron beamlines and free electron lasers) and the use of electrons to extend protein crystallography to ever decreasing crystal sizes; and an increase in the resolution attainable by cryo‐electron microscopy. Here we discuss the use of these techniques in general terms and highlight their application for biological filament systems, an area that is severely underrepresented in atomic resolution structures. We assemble a model of a capped tropomyosin‐actin minifilament to demonstrate the utility of combining structures determined by different techniques. Finally, we survey the methods that attempt to transform high resolution structural biology into more physiological environments, such as the cell. Together these techniques promise a compelling decade for structural biology and, more importantly, they will provide exciting discoveries in understanding the designs and purposes of biological machines. Abstract : Structural biology is undergoing technological advancements that now reveal the structures of previously inaccessible biological machines. Microfocus synchrotron beamlines, X‐ray free electron lasers, and MicroED cope with vanishingly small crystals, while cryo‐electron microscopy (cryoEM) targets single molecules at near atomic resolution. These advances promise an exciting decade for structural biology.